In Silico identification and characterization of SOS gene family in soybean: Potential of calcium in salinity stress mitigation - Anam Hameed; M. Asaf Khan; M. Hammad Nadeem Tahir; Madeeha Shahzad Lodhi; Saima Muzammil; Muhammad Shafiq; Tsanko Gechev; Muhammad Faisal (PLoS ONE, 2025)
Leguminous crops are usually sensitive to saline stress during germination and plant growth stages. The Salt Overly Sensitive (SOS) pathway is one of the key signaling pathways involved in salt translocation and tolerance in plants however, it is obscure in soybean. The current study describes the potential of calcium application on the mitigation of salinity stress and its impact on seed germination, morphological, physiological and biochemical attributes of soybean. The seeds from previously reported salt-tolerant and salt-susceptible soybean varieties were primed with water, calcium (10 and 20 mM), and stressed under 60, 80 and 100 mM NaCl and evaluated in various combinations. Results show that germination increased by 7% in calcium primed non-stressed seeds under non-stressing, whereas an improvement of 15%-25% was observed in germination under NaCl stress. Likewise, improvement in seedling length (3%-8%), plant height (9%-18%), number of nodes (3%-14%), SOD activity (20%) and Na+/K+ concentration (3%-5% reduction) in calcium primed plants, indicates alleviation of salinity-induced negative effects. In addition, this study also included in silico identification and confirmation of presence of Arabidopsis thaliana SOS genes orthologs in soybean. The research of amino acid sequences of SOS proteins from Arabidopsis thaliana (AtSOSs) within Glycine max genome displayed protein identity (60–80%) thus these identified homologs were called as GmSOS. Further phylogeny and in silico analyses showed that GmSOS orthologs contain similar gene structures, close evolutionary relationship, and same conserved motifs, reinforcing that GmSOSs belong to SOS family and they share many common features with orthologs from other species thus may perform similar functions. This is the first study that reports role of SOSs in salt-stress mitigation in soybean.